An Analytical Study of GLARE Cantilever Beams Under Low Velocity Impact - Al-Kasob, Bashar Dheyaa Hussein; Al-Obaidi, Ali Assim; Salaman, Ali Jahel (Journal of Applied Nonlinear Dynamics, 2026)
Low velocity impact response of GLARE (GLAss REinforced aluminium laminate) beam based on First Order Shear Deformation Theory is studied. The system energy is written and using Ritz method and generalized Lagrange equations, the motion equations are derived. Good agreement is achieved between this analytical method and available results. Results reveal that an increase of the impactor initial velocity causes increasing in the peak of contact force and peak of central beam deflection but decreasing contact time. Also, increasing of the impactor radius will enhances the peak of contact force and diminish peak of central beam deflection and contact time.